2009
DOI: 10.1159/000258078
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Cardiovascular Symptoms: The Modulating Role of Insomnia

Abstract: Background: Anxiety and insomnia are associated with cardiovascular (CV) symptoms. We assessed whether the relation between anxiety and CV symptoms is modulated by insomnia. Methods: Independently living women (n = 1,440; mean age = 59.36 ± 6.53 years) were recruited by cluster sampling technique. We obtained data on demographic characteristics, health beliefs, access to health care, CV symptoms, sleep, stress and anxiety levels. Results: Overall, 56% of the sample reported insomnia; 46% reported CV symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
1
6
0
1
Order By: Relevance
“…By contrast, most studies in adolescents and adults demonstrated that females are more vulnerable to insomnia symptoms. [ 1 , 2 , 11 ] A study specifically examined the gender difference in insomnia, indicated that gender difference in insomnia maybe occur only after puberty [ 4 ]. In additional, our study found an age-dependent increasing tendency in the prevalence of FNA in our studied age group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, most studies in adolescents and adults demonstrated that females are more vulnerable to insomnia symptoms. [ 1 , 2 , 11 ] A study specifically examined the gender difference in insomnia, indicated that gender difference in insomnia maybe occur only after puberty [ 4 ]. In additional, our study found an age-dependent increasing tendency in the prevalence of FNA in our studied age group.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that psychological variables can play predisposing role in the onset and development of insomnia [ 35 ]. Although the association between psychological functioning and insomnia was well established in adults [ 1 , 2 , 7 , 9 11 ], litter is known in childhood. Only one study in children aged 6 to 13 years reported that frequent temper outburst was a risk factor for childhood insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one could not exclude a potential survival bias of those people who experience anxiety during the lifespan. The higher risk of cardiovascular events and premature cardiovascular-related death among people suffering from anxiety could then significantly decrease life expectancy of people suffering from anxiety disorders [49].…”
Section: Potential Underlying Biological Mechanismsmentioning
confidence: 99%
“…The availability of social support to overcome stressors that impact sleep is also important. Although not well studied, sleep is also likely to be influenced by psycho-social interactions within households, such as chaotic family routines, mother-child stress, the level of autonomy allowed and practiced by each family member, and poor sleep patterns of family members (69; 70; 147) --which may influence stress responses leading to increased arousal, a known mediator of disturbed sleep (123; 146). …”
Section: A Conceptual Framework For the Role Of Sleep In Cardiovasculmentioning
confidence: 99%